Biostabilization of cadmium contaminated sediments using indigenous sulfate reducing bacteria: Efficiency and process. (June 2018) - Peng, Weihua; Li, Xiaomin; Liu, Tong; Liu, Yingying; Ren, Jinqian; Liang, Dawei; Fan, Wenhong
Abstract: Sulfate reducing bacteria (SRB) was used to stabilize cadmium (Cd) in sediments spiked with Cd. The study found that the Cd in sediments (≤600 mg kg −1 ) was successfully stabilized after 166 d SRB bio-treatment. This was verified by directly and indirectly examining Cd speciation in sediments, mobilization index, and Cd content in interstitial water. After 166 d bio-treatment, compared with control groups, Cd concentrations in interstitial water of Cd-spiked sediments were reduced by 77.6–96.4%. The bioavailable fractions of Cd (e.g., exchangeable and carbonate bound phases) were reduced, while more stable fractions of Cd (e.g., Fe-Mn oxide, organic bound, and residual phases) were increased. However, Cd mobilization in sediment was observed during the first part of bio-treatment (32 d), leading to an increase of Cd concentrations in the overlying water. Bacterial community composition (e.g., richness, diversity, and typical SRB) played an important role in Cd mobilization, dissolution, and stabilization. Bacterial community richness and diversity, including the typical SRB (e.g., Desulfobacteraceae and Desulfobulbaceae ), were enhanced. However, bacterial communities were also influenced by Cd content and its speciations (especially the exchangeable and carbonate bound phases) in sediments, as well as total organic carbon in overlying water. Graphical abstract: Image 1 Highlights: Cd bioavailable fractions were reduced, while more stable fractions increased. Cd mobilization occurred early, but stabilized after 166 days of bioremediation. Cd bioavailable fractions were important to bacterial community composition. Desulfobacteraceae and Desulfobulbaceae were enhanced during biostabilization.